Creating Dialogue between Science and Religion - Abdullah, Salar Ziro (International Journal of English Literature and Social Sciences (IJELS), 2019)
Searching for common ground in philosophy, science and theology, it seems to us that it would be reasonable to maintain the position of realistic pragmatism that Charles Sanders Peirce had called pragmaticism. In the pragmaticist manner, we typify the knowledge and select the types of knowledge that might be useful for understanding the problems that are of interest to us. We pose a question of how it would be possible to obtain practically useful information about reality, first from the perspective of natural sciences, and then from that of theology; that is, to diversify the ways of knowledge and just maybe, to move toward a productive dialogue between science and religion. Searching for common ground in philosophy, science and theology, it seems to us that it would be reasonable to maintain the position of realistic pragmatism that Charles Sanders Peirce had called pragmaticism. In the pragmaticist manner, we typify the knowledge and select the types of knowledge that might be useful for understanding the problems that are of interest to us. We pose a question of how it would be possible to obtain practically useful information about reality, first from the perspective of natural sciences, and then from that of theology; that is, to diversify the ways of knowledge and just maybe, to move toward a productive dialogue between science and religion.